Habituation of evoked potentials in the rat under conditions of behavioral control - Hall, Robert D (Electroencephalography and clinical neurophysiology, 1968)
Three experiments are reported in which potentials evoked by sensory stimuli were recorded from rats during habituation procedures. In all three, behavior was controlled through the use of appetitive operant conditioning procedures. In one experiment rats were exposed to repetitive photic stimuli, and evoked potentials were recorded from primary visual cortex. In two experiments rats were exposed to repetitive click stimulation, and evoked potentials were recorded from auditory cortex and, in various subjects, from medial geniculate body, inferior colliculus, ventral cochlear nucleus, and mesencephalic reticular formation. Constant rates of behavioral responding provided a control against fluctuations in the level of arousal, and the nature of the behavioral responses indured a relatively constant orientation of the subjects with respect to the stimuli. The photic and acoustic stimuli were irrelevant to the behavioral tasks. Average evoked responses revealed the following: 1. 1. Photically evoked potentials recorded from visual cortex exhibited habituation, and the amplitude reductions were confined to late components of the evoked response. 2. 2. Click-evoked potentials recorded from auditory cortex and medial geniculate body also showed reductions in amplitude during repetitive stimulation. At the cortical level the amplitude changes involved only late components of the evoked response. 3. 3. Click-evoked potentials recorded from the inferior colliculus, ventral cochlear nucleus (both VIIIth nerve and cochlear nucleus components), and reticular formation did not show consistent evidence of habituation. 4. 4. The data appear to justify the conclusion that habituation of evoked potentials occurs in the classical sensory pathways, but is probably restricted to cortical and thalamic levels of the sensory systems. These changes cannot be attributed to changes in the level of arousal, uncontrolled fluctuations in stimulus intensity, or “pre-receptor” mechanisms. Les auteurs relatent trois expériences lors desquelles des potentiels évoqués par des stimuli auditifs sont enregistrés sur des rats pendant des protocoles d'habituation. Dans toutes les trois, le comportement est controllé par l'utilisation de protocole de conditionnement opérant alimentaire. Dans une expérience les rats sont exposés à des stimuli visuels et les potentiels évoqués enregistrés depuis le cortex visuel primaire. Dans deux expériences les rats sont exposés à une stimulation répétitive par des clicks, et les potentiels évoqués sont enregistrés depuis le cortex auditif et chez des sujets variés, depuis le corps géniculé médian, le colliculus inférieur, le noyau cochléaire ventral, et la formation réticulée mésencéphalique. Des degrés constants de réponses comportementales fournissent un contrôle des fluctuations du niveau d'éveil, et la nature des réponses comportementales assure une orientation relativement constante des sujets en rapport avec les stimuli. Les stimuli visuels et auditifs sont sans rapport avec les tâches comportementales. Les réponses évoquées moyennes révèlent: 1. 1. Les potentiels évoqués visuels enregistrés depuis le cortex visuel manifestent une habituation, et les réductions d'amplitude sont réduites aux composantes tardives de la réponse. 2. 2. Les potentiels évoqués par les clicks enregistrés depuis le cortex auditif et le corps géniculé médian, montrent aussi une réduction d'amplitude lors de stimulations répétitives. Auniveau cortical les variations d'amplitude affectent seulement les composantes tardives de la réponse évoquée. 3. 3. Les réponses évoquées par les clicks enregistrées depuis le colliculus inférieur, le noyau cochléaire ventral (aussi bien le 8me nerf et les composantes du noyau cochléaire) et de la formation réticulaire ne montrent de preuve claire d'habituations. 4. 4. Les données semblent justifier la conclusion que l'habituation des potentiels évoqués apparait dans les voies sensorielles classiques, mais ent probablement limitée aux niveaux cortical et thalamique des systèmes sensoriels. Ces variations ne peuvent être attribuées à des variations du niveau d'éveil, à des fluctuations incontrollées dans l'intensité du stimulus, ou aux mécanismes pré-récepteurs.